Practicality Study of E-Learning Development on Electrolyte and Non-Electrolyte Solution Using the Flipped Classroom-Project Based Learning Approach in Senior High School - Oladele Bola; Annisa Aulia; Fanny Azhari Formen; Oshin Amirah Rafi; Yusnel Yusnel (Center For Advanced Material Processing, Artificial Intelligence, Biophys-Informatics (CAMPBIOTICS), Universitas Negeri Padang, 2021)
E-learning of the electrolyte and non-electrolyte solutions based on project-based learning used the flipped classroom approach have been developed and analyzed for their validity and practicality assist the learning process of students. This research belongs to research and development with Plomp model. E-learning is validated by three media expert validators and by twenty students to test its practicality. The research instrument used was validity and practicality questionnaire. Populations in this research are students from Senior High School in West Sumatera, Indonesia. There are 20 students of SMA N 8 Padang, in X class level as respondents for developing this product. Data were analyzed using Aiken V and precent of student’s understanding. The results of the content and construct validity test obtained an average value of V of 0,86. the result of practicality obtained a percent of student’s understanding obtained an average value of 0,83. these data indicate that e-learning that has been developed is valid and practical. The results of the study stated that e-learning developed was valid and practical so that its effectiveness could be tested